STRATEGI PENGENDALIAN ECENG GONDOK (Eichornia crassipes)DI PERAIRAN WADUK JATILUHUR, JAWA BARAT - Ezra Fajar Dewantara; Yanuar Jarwadi Purwanto; Yudi Setiawan (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2021)
Indonesia has quite extensive multi-purpose reservoir waters, one of which was built for the first time is the Ir. H. Djuanda reservoir or better known as Jatiluhur reservoir. The activities carried out in the Jatiluhur reservoir are varied, such as fisheries, transportation,water sources as well as power generation as secondary functions of the reservoir. If managed properly, the reservoir will give a real contribution to the economy and welfare of the community without disrupting the sustainability of the ecosystems and its functions. In Indonesia, problems that often occur in all aquatic ecosystems are eutrophication (nutrient enrichment), sedimentation, and pollution. Water hyacinth (Eichorniacrassipes) is a type of aquatic plant that is generally considered as a weed. The study aims to formulate a water hyacinth management strategyusing the SWOT method with ten respondents.The selection of respondents using purposive sampling method.The results showed that all stakeholders, government, and communities must work together in utilizing and managing reservoirs and watersheds that enter the reservoir waters so that the quality status of reservoir becomes better and the growth of water hyacinth does not increase rapidly. Water hyacinth can also be used as fertilizer or crafts and not just a weed.